2017
DOI: 10.1128/mmbr.00033-16
|View full text |Cite
|
Sign up to set email alerts
|

Random versus Cell Cycle-Regulated Replication Initiation in Bacteria: Insights from Studying Vibrio cholerae Chromosome 2

Abstract: SUMMARY Bacterial chromosomes initiate replication at a fixed time in the cell cycle, whereas there is generally no particular time for plasmid replication initiation or chromosomal replication initiation from integrated plasmids. In bacteria with divided genomes, the replication system of one of the chromosomes typically resembles that of bacteria with undivided genomes, whereas the remaining chromosomes have plasmid-like replication systems. For example, in Vibrio cholerae, a bacterium with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 99 publications
0
32
0
Order By: Relevance
“…The first goal of this review is to build upon previous reviews (11,(23)(24)(25)(26)(27)(28)(29)(30)(31) and to provide an unbiased assessment of the information available on the structure, function, and evolution of divided bacterial genomes. This consists of a comprehensive review of the relevant literature as well as an analysis of all complete genomes available through the National Center for Biotechnology Information (NCBI) genome database (accessed 21 March 2016) as a way of reviewing the abundant, untapped information present within these sequences.…”
Section: Purpose Of This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The first goal of this review is to build upon previous reviews (11,(23)(24)(25)(26)(27)(28)(29)(30)(31) and to provide an unbiased assessment of the information available on the structure, function, and evolution of divided bacterial genomes. This consists of a comprehensive review of the relevant literature as well as an analysis of all complete genomes available through the National Center for Biotechnology Information (NCBI) genome database (accessed 21 March 2016) as a way of reviewing the abundant, untapped information present within these sequences.…”
Section: Purpose Of This Reviewmentioning
confidence: 99%
“…The term "chromid" itself is a combination of chromosome and plasmid (11) and underscores how chromid refers to a replicon that is an intermediate between a plasmid and a chromosome (11). The replication systems of chromids are similar to those of plasmids and megaplasmids (11) but may have additional regulatory controls that integrate their replication into the cell cycle (29,36,37). However, unlike plasmids and megaplasmids, chromids carry at least one gene that is essential for cell viability (i.e., a core gene whose loss would result in cell death) and generally have genomic signatures that better resemble those of the chromosome (11).…”
Section: Chromidmentioning
confidence: 99%
“…As there are many bacterial species with multiple chromosomes that are being discovered, there is an accumulating interest in understanding how the faithful segregation of chromosomes is coordinated with cell division, and V. cholerae has emerged as a model to address these questions (39, 66, 108). Chromosome 1, the larger chromosome, communicates with chromosome 2 and signals the proper time to initiate DNA replication while undergoing its own replication (6, 109, 135). A recent report has provided evidence that mutants that lack both Min and NO systems are viable (51).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the family Rhizobiaceae exhibit signs of replicon co-evolution (Slater et al 534 2009; Lassalle et al 2017;Wang et al 2018) and cross-replicon interactions (Ronson et 535 al. 1987;Heidelberg et al 2000;Barnett et al 2004;Bobik et al 2006;Galardini et al 536 2015; Pini et al 2015;Ramachandran et al 2017;diCenzo et al 2018), despite 537 remarkable strain-to-strain variation and the prevalence of large-scale rearrangements 538 in secondary replicons (Orozco-Mosqueda Mdel et al 2009;Mazur et al 2011;Lopez-the Ti plasmid of a different octopine-type strain of A. tumefaciens (Machida et al 1984) 562 and is part of a larger family of IS-elements found within a variety of bacteria (Han et al 563 2001; Gourbeyre et al 2010). IS-elements are common vehicles for genome 564 rearrangements and responsible for genome reduction in many bacterial taxa, including 565 species of Bordatella (Parkhill et al 2003;Siguier et al 2006).…”
mentioning
confidence: 99%